1971
DOI: 10.1029/ja076i007p01738
|View full text |Cite
|
Sign up to set email alerts
|

Rocket measurement of the secondary electron spectrum in an aurora

Abstract: To be published in the Journal of The differential flux of secondary electrons with energy greater than 6 e V w a s measured in a steady I aurora with an electron spectrometer aboard an Aerobee rocket. range 10-20 eV, the observed spectrum is in excellent agreement with a recent theoretical prediction. About one-half of the observed N2+ emission at 3914 A can be accounted for by secondary electron excitation.Except for the absence of structure in the energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Theoretical [Rees et al, 1969;Banks et al, 1974] and experimental [Opal et al, 1971] descriptions of the secondary electron production processes have been developed and used to predict auroral emission intensities [Rees and Jones, 1972;Sharp and Rees, 1972]. Feldman et al [1971] reported a measurement of the differential electron flux above 7 V. They found that the structure predicted by theory was not present in the data.…”
mentioning
confidence: 99%
“…Theoretical [Rees et al, 1969;Banks et al, 1974] and experimental [Opal et al, 1971] descriptions of the secondary electron production processes have been developed and used to predict auroral emission intensities [Rees and Jones, 1972;Sharp and Rees, 1972]. Feldman et al [1971] reported a measurement of the differential electron flux above 7 V. They found that the structure predicted by theory was not present in the data.…”
mentioning
confidence: 99%
“…An additional concern is that the existence of the EA and ECS mode requires comparable fractions of hot and cold populations. While secondary auroral electrons do provide a warm population of electrons, their densities are typically on the order of a few percent [Rees, 1969;Feldman et al, 1971;Gérard, 1972], though this has only a minor impact on the mode dispersion. Auroral electron energies (∼1-10 s of keV) meet cyclotron resonance conditions for n = 1 and n = 2, but only lower energy electrons (100 s of eV) satisfy Landau resonance with these modes.…”
Section: Discussionmentioning
confidence: 99%
“…The differential flux of primary and secondary electrons under auroral activity has been the subject of a series of experimental measurements [Feldman et al, 1972;Arnoldy and Choy, 1973;Reasoner and Chappell, 1973;Feldman and Doering, 1975;Matthews et al, 1976]. A common feature of all these rocket experiments is that between 30 and 85 eV, where the measurements overlap in energy, the electron flux data can be fitted by a power law E -• with 0.5 < a < 1.0.…”
Section: Introductionmentioning
confidence: 99%